2022
DOI: 10.3390/antibiotics11081009
|View full text |Cite
|
Sign up to set email alerts
|

Current and Potential Therapeutic Options for Infections Caused by Difficult-to-Treat and Pandrug Resistant Gram-Negative Bacteria in Critically Ill Patients

Abstract: Carbapenem resistance in Gram-negative bacteria has come into sight as a serious global threat. Carbapenem-resistant Gram-negative pathogens and their main representatives Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa are ranked in the highest priority category for new treatments. The worrisome phenomenon of the recent years is the presence of difficult-to-treat resistance (DTR) and pandrug-resistant (PDR) Gram-negative bacteria, characterized as non-susceptible to all conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…The major problem is their limited commercial availability. Εravacycline is unavailable in Europe and cefiderocol has only been recently launched in a few European countries (United Kingdom, Germany and Italy), mostly serving compassionate use purposes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major problem is their limited commercial availability. Εravacycline is unavailable in Europe and cefiderocol has only been recently launched in a few European countries (United Kingdom, Germany and Italy), mostly serving compassionate use purposes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While double-carbapenem treatment is sometimes referred to as a therapeutic option, clinical evidence is lacking [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Moreover, in vitro data on the synergistic effects are conflicting, and there is a lack of consensus on which carbapenems should be combined to best counteract the different enzymes [ 12 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several trichogin analogs were found to be active against epidemiologically relevant MDR and XDR clinical isolates, including WHO "critical priority" pathogens for antibiotic research and development, with negligible hemolytic activity. The peptides were also active against XDR P. aeruginosa, against which only a limited number of antibiotics currently under development are active [55,56]. A structure-activity relationship built on CD analysis under different experimental conditions indicated that a well-defined helical conformation in water is needed for the peptides to exert their antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%